A frog's life cycle - Thomson, Ruth, 1949- (New York : PowerKids Press, 2010)
This book describes the life cycle of a frog from frogspawn to adult frog.
Frogs gather - Frogspawn - Time to hatch - Tadpoles - Food - Legs grow - Froglet - Frog - Winter and spring - Frog life cycle - Make a pop-up card.
Includes glossary.
Includes bibliographical references (p. 24) and index.
K-3
Accelerated Reader AR
Keywords: Frogs -- Life cycles; Life cycles (Biology)